Camptopoeum (Camptopoeum) baldocki spec. nov., a new panurgine bee species from Portugal and a description of the male of Flavipanurgus fuzetus Patiny (Andrenidae: Panurginae) - Wood, Thomas. J.; Cross, Ian (Zootaxa, 2017)
Camptopoeum (Camptopoeum) baldocki spec. nov., a new European panurgine bee species is described and diagnosed. It is currently known only from saltmarshes along the southern coast of the central and eastern Algarve, Portugal. Observations and analysis of scopal pollen loads suggest narrow oligolecty on the similarly halophilous Frankenia laevis (Frankeniaceae). In addition, the allotype male of the Portuguese endemic Flavipanurgus fuzetus Patiny is described and the pollen preferences of Flavipanurgus are reviewed with the addition of new data from Portugal. As a genus, Flavipanurgus species appear to be narrowly oligolectic on a range of flowers from the botanical families Caryophyllaceae, Cistaceae and Crassulaceae.